Answer:
The equivalent of -1/3t = 4/3 is t = -4
Solution:
Need to determine such value of t so that when it is multiplied by -1/3, we should get 4/3
That is we need to solve following expression for value of t.
![-(1)/(3) t=(4)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iprkmw7r38j0p1djqvsxnj677pw9e7fy29.png)
On multiplying both the sides by 3 we get
![\begin{array}{l}{-(1)/(3) t * 3=(4)/(3) * 3} \\\\ {=>-t=4}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1kuhkqxfvzh1j8z3gdatzir93yhad46k09.png)
Now multiplying both the sides by -1 we get
![\begin{array}{l}{-t *-1=4 *-1} \\ {=>t=-4}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k5a6b6rz7wswmbqv9nopvgu3xzy309eh5e.png)
Let’s recheck the value of t
![-(1)/(3) t=-(1)/(3) *-4=(4)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g9szr2a38wbtogzj7g3bj88cx0se1yrbdj.png)
Hence for t = -4, expression -1/3 t is equal to 4/3.